Design of a Tracking Controller for Object Interception in Space - Jarzębowska, Elżbieta; Pilarczyk, Bartłomiej (Discontinuity, Nonlinearity, and Complexity, 2026)
The paper presents a model-based tracking controller design for a freefloating space robot for a mission scenario of intercepting an object. Such missions are of interest due to a growing number of objects needed to be removed from space. The free-floating mode requires spacecraft thrusters to be off and linear and angular momentum are conserved then. Momentum conservation generates holonomic and nonholonomic constraint equations, respectively. The free-floating mode implicates underactuation, so the robot becomes multi-constrained. Many control algorithms are designed for underactuated robots but they are specific mission and robot dependent. Motivations for the presented research come from the growing space exploration, which results in more space debris and requires sophisticated removal services. Service tasks and debris removal need to be performed by specialized robots. The debris interception scenario presented in the paper consists of estimation of target properties, a controller design to track and intercept the debris, and move it to the graveyard orbit. Simulation results of the theoretical control development for the robot intercepting a non-tumbling object are provided.